Analisis Finansial dan Pemasaran Pakkat dari Rotan Seel (Daemonorops melanochaetes Bl.) di Kecamatan Simangambat, Kabupaten Padang Lawas Utara - Hafnita Misrawati Harahap; Agus Purwoko; Yunus Afifuddin (Peronema Forestry Science Journal, 2014)
Rattan is one of non timber forest products. Almost all parts can be used, one of it was processed into pakkat. Today, information of pakkat economic value is limitted, so that people were uninterested in process it. Therefore, this research aimed to determine the financial feasibility, workflow and marketing margins and marketing efficiency pakkat. The research was conducted in Simangambat Sub District, Padang Lawas Utara District. Respondents of this study is pakkat coolector and traders. The method of data analysis were financial analysis and marketing analysis. The Results showed that the effort is feasible for pakkat cultivating, because the value of R / C ratio of more than one volume is 1,5 with BEP production by 790 units and BEP price of Rp. 392.50, and the period after the return of capital is 2,71 times the production. Pakkat marketing groove starts from farmers, collectors, retailers, and finaly to consumers. There are 2 lines with margin value was Rp. 900,00.